ROTATING MEMBRANE EMULSIFICATION FOR PRODUCING UNIFORM EMULSION - Aryanti, Nita (Universitas Diponegoro, 2011)
Abstract A versatile and high capacity membrane emulsification system which utilises a rotating membrane for the precision manufacture of uniform emulsions droplet was investigated. Single emulsions were produced with a very low viscosity of paraffin wax. Tween 20 and carbomer, as dispersed phase, emulsifier and stabilizer, respectively. Emulsion droplets in the range of 138 µm to 305 µm with coefficient of variation (CV) ranging from 9% to 29% were obtained. The methodology allows control of droplet production through adjustment of system operating parameters (membrane type, rotation speed, dispersed phase flux) to influence the average droplet size and droplet uniformity. Keywords : Emulsion, membrane emulsification, rotating membrane, stainless steel membrane, uniform droplet.